1998
DOI: 10.1007/bf02780969
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the “molecular trap” of protease-catalyzed splicing reaction of complementary segments of α-subunit of hemoglobin A

Abstract: The complementary fragments of human Hb alpha, alpha1-30, and alpha31-141 are spliced together by V8 protease in the presence of 30% n-propanol to generate the full-length molecule (Hb alpha-semisynthetic reaction). Unlike the other protease-catalyzed protein/peptide splicing reactions of fragment complementing systems, the enzymic condensation of nonassociating segments of Hb alpha is facilitated by the organic cosolvent induced alpha-helical conformation of product acting as the "molecular trap" of the splic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Recent studies have demonstrated that ceramide increased in endothelial cells exposed to death factors, including tumor necrosis factor α , interleukin 2, and endostatin, and in ischemic reperfused myocardium [46, 47]. In these studies, the ceramide signaling pathway has been confirmed to be involved in the activation of Nox and consequent O 2 − production [48, 49]. Ceramide also enhances ROS formation in mammalian cells by straightly raising the permeability of mitochondrial membranes to cytochrome c [50] and restraining the isolated mitochondria complex III [51].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that ceramide increased in endothelial cells exposed to death factors, including tumor necrosis factor α , interleukin 2, and endostatin, and in ischemic reperfused myocardium [46, 47]. In these studies, the ceramide signaling pathway has been confirmed to be involved in the activation of Nox and consequent O 2 − production [48, 49]. Ceramide also enhances ROS formation in mammalian cells by straightly raising the permeability of mitochondrial membranes to cytochrome c [50] and restraining the isolated mitochondria complex III [51].…”
Section: Discussionmentioning
confidence: 99%
“…They are also extensively used for studying enzyme active centres (Ma et al, 2002;Seeley et al, 2005) and as catalysts of enzymatic synthesis (Bonger and Lambros, 1994;Wehofsky et al, 2001). For instance, proteinase V8 from Staphylococcus aureus is capable of catalysing the oligomerization reaction of native protein segments of ribonuclease, as well as condensation of complementary fragments of human haemoglobin molecule (Sahni et al, 1998;Kumaran et al, 2000). Glutamyl endopeptidases can also be utilised for the synthesis of synthetic peptides used as substrates for proteinases (Braddam and Meldal, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, the obtention of these two peptides from haemoglobin has never been reported. V8 protease has been widely employed for fragmentation of proteins prior to amino‐acid‐sequence determination and as catalyst for the synthesis of specific peptide bonds [13–16]. It has proved to be eminently suitable for generating digests which contain many appropriately sized peptide fragments, as it exhibits a high degree of specificity for the Glu and Asp residues of peptides and proteins [17,18].…”
Section: Introductionmentioning
confidence: 99%